Analysis of coping capacities and cognitive biases of novice drivers—A questionnaire-based study - Xiang, Wang; Zhang, Yonghe; Pan, Xin; Liu, Xuemei; Xu, Guiqiu (PloS one, 2024)
Coping capacity is a key aspect of driver-vehicle interaction when drivers observe and make decisions, and is of great importance for drivers. However, different drivers have different self-cognition and assess their driving abilities differently, especially for novice drivers. Based on questionnaire data, this study has investigated the coping capacities of drivers in both static environments and dynamic environments. With the ANOVA analysis method and the structural equation model (SEM), this study has verified the effects of gender and driving factors (driving years, driving frequency, driving time) on drivers’ coping capacities based on drivers’ self-assessment scores and mutual assessment scores. Drivers’ self-assessment scores show significant effects of all factors on drivers’ coping capacities, and drivers’ mutual assessment scores show significant effects of all factors, excluding driving time, on drivers’ coping capacities. Also, it has been found that all drivers in the driving year group have cognitive biases. It seems that first-year drivers are always overconfident with their driving skills, while drivers with a driving experience of more than three years usually score driving skills of themselves and other drivers most conservatively. With increased exposure to various traffic conditions, experienced drivers are more aware of their limitations in dealing with complex traffic situations, while novice drivers do not know their lack of capability to properly respond to any unexpected situation they could encounter.